2019
DOI: 10.1111/sms.13424
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maximal fat oxidation during exercise: A systematic review

Abstract: Maximal fat oxidation during exercise (MFO) and the exercise intensity eliciting MFO (Fatmax) are considered biological markers of metabolic health and performance. A wide range of studies have been performed to increase our knowledge about their regulation by exercise and/or nutritional intervention. However, numerous data collection and analysis approaches have been applied, which may have affected the MFO and Fatmax estimation. We aimed to systematically review the available studies describing and/or compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 63 publications
(126 reference statements)
2
44
1
1
Order By: Relevance
“…Further, although the graded exercise protocol used to assess MFO and Fat max was similar in both studies, Venables et al established a fasting time of 4 hours before starting the test, and used measured-values data analysis to estimate MFO and Fat max , whereas in the present work a fasting time of 5-6 hours was established and 3rd polynomial curve analysis used to estimate MFO and Fat max , in agreement with the most updated methodological consensus 29,36. Finally, Venables et al made no adjustment for VO 2 max, which is known to play a key role.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Further, although the graded exercise protocol used to assess MFO and Fat max was similar in both studies, Venables et al established a fasting time of 4 hours before starting the test, and used measured-values data analysis to estimate MFO and Fat max , whereas in the present work a fasting time of 5-6 hours was established and 3rd polynomial curve analysis used to estimate MFO and Fat max , in agreement with the most updated methodological consensus 29,36. Finally, Venables et al made no adjustment for VO 2 max, which is known to play a key role.…”
supporting
confidence: 66%
“…[13][14][15]18,[28][29][30]37 However, other authors suggest that 3 minutes might not be long enough to reach a steady metabolic state in very sedentary patients, which would affect any estimate of MFO and Fat max . It is noteworthy that the assessment of sedentary time and PA, 27 as well as the estimation of MFO and Fat max 29,36 were, however, performed in keeping with the latest methodological consensus. It has recently been proposed that there is diurnal variation in MFO, 28 which if true could have had an impact on the present results.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…A walking graded test on a treadmill (H/P/cosmos pulsar, H/P/cosmos sports & medical GmbH, Nussdorf-Traunstein, Germany) was performed to calculate MFO and FATmax following a previously validated methodology 35 . Briefly, the protocol started assessing the maximal walking speed of each participant [35][36][37] . After ~3 minutes resting, the walking graded test started with a 3-minute warm up at 3.5 km/h.…”
Section: Maximal Fat Oxidation During Exercise Assessment Mfo and Thmentioning
confidence: 99%
“…Maximal carbohydrate oxidation was not included in the analyses since it is not a key factor of energy metabolism during exercise 39 . Indeed, our recent systematic review has analyzed a total of 112 studies which included data about fuel oxidation during exercise 37 . None of those studies reported maximal carbohydrate oxidation during exercise.…”
Section: Maximal Fat Oxidation During Exercise Assessment Mfo and Thmentioning
confidence: 99%
“…Subsequently, VO 2 , VCO 2 and ventilation data were averaged over the last 60 s of each 2-min stage and stoichiometric equations described by Frayn [22] were used to calculate fat oxidation rates with the assumption that urinary nitrogen excretion was negligible. Fat oxidation rates were then plotted against the relative exercise intensity ( %VO 2 peak) and a third-degree polynomial regression was used to determine maximal fat oxidation (MFO) and the exercise intensity eliciting MFO (FAT max ) for each participant [23]. MFO was normalized to lean body mass (mg/min/kg LBM).…”
Section: Cardiopulmonary Exercise Testmentioning
confidence: 99%